THE CORE VALUES OF CHINA’S «CULTURAL SOFT POWER» CONCEPT: NATIONAL CHARACTERISTICS AND UNIVERSALITY - K. A. Tarabarko (Дискурс, 2016)
The article substantiates the idea that the traditional values, that are the fundamental for the ethos of Chinese culture, constitute the axiological bases of China’s «cultural soft power» concept and determine the specific nature of the Chinese «soft power» theory in general. Particular attention is paid to the analysis of the basic traditional values in their modern interpretation. The author concludes that the Chinese cultural soft power has significant societal resources that are capable to ensure the integrity and stability of China’s internal development and to enhance its competitiveness to represent cultural and value bases for the global development harmonization.